2004
DOI: 10.1161/01.hyp.0000124668.80811.d3
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Inhibits C-Type Natriuretic Peptide Activation of Guanylyl Cyclase B (GC-B/NPR-B)

Abstract: Abstract-C-type natriuretic peptide (CNP) binds and activates the transmembrane guanylyl cyclase B receptor (NPR-B), which decreases vascular tone and inhibits cell proliferation and migration. In contrast, the bioactive lipid sphingosine-1-phosphate (S1P) elicits the opposite physiological effects. Here, we demonstrate a potent acute inhibitory effect of S1P on NPR-B activity in NIH3T3 fibroblasts and A10 vascular smooth muscle cells. In fibroblasts, S1P reduced CNP-dependent cGMP elevations to the same level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…CNP infusions reduce intimal thickening and restenosis after experimental balloon angioplasty injury to vessels. 26 This report 25 indicates S1P, a novel phospholipid signaling molecule released in micromolar concentrations from activated platelets, inhibits GC-B in both fibroblasts and VSMCs. This appears to be the most potent GC-B desensitizing factor identified to date.…”
Section: Gc-b Receptormentioning
confidence: 86%
See 1 more Smart Citation
“…CNP infusions reduce intimal thickening and restenosis after experimental balloon angioplasty injury to vessels. 26 This report 25 indicates S1P, a novel phospholipid signaling molecule released in micromolar concentrations from activated platelets, inhibits GC-B in both fibroblasts and VSMCs. This appears to be the most potent GC-B desensitizing factor identified to date.…”
Section: Gc-b Receptormentioning
confidence: 86%
“…Abbey-Hosch et al 25 demonstrated that sphingosine-1-phosphate (S1P) inhibits GC-B activity. Administration of CNP in whole animal or isolated vascular models induces a reduction in vascular tone and longer term effects include inhibition of vascular smooth muscle cell (VSMC) proliferation and migration.…”
Section: Gc-b Receptormentioning
confidence: 99%
“…We recently demonstrated that the arginine-, vasopressin-, and sphingosine-1-phosphatedependent desensitization of NPR-B requires elevated calcium concentrations (17,25). Therefore, we asked whether calcium also mediates the hyperosmotic effect.…”
Section: Calcium Elevations Are Required For Hyperosmotic and Lpadepementioning
confidence: 99%
“…The factor was purified and shown to be S1P [46]. The work of AbbeyHosch et al [56] has also shown that S1P can induce desensitization of GCB. S1P is bound principally to high-density lipoprotein (HDL) in serum, where its concentrations (if all considered unbound to protein) range between 500-1000 pM.…”
Section: Clinical Implications Of C-type Natriuretic Peptidementioning
confidence: 99%
“…There are five putative S1P receptors, all apparently coupled to G proteins (Figure 3). Importantly, the desensitization of GCB caused by either serum or S1P is pertussis toxin insensitive [45,46,56]. The most widely distributed receptors, S1PR1-S1PR3, have been suggested to couple to pertussis toxin-sensitive Gi or Go, or insensitive Gq and G12 or G13 [57][58][59][60][61].…”
Section: S1p Signaling Pathwaysmentioning
confidence: 99%